Impact of Organizational Culture and Training on The Employee Performance of PT. Kokoh Semesta: Job Satisfaction as A Mediation Variable - Yulia Elvi Prada; Deden Kurniawan (Dinasti International Journal of Management Science, 2023)
Basically, this study aims to examine and analyze the importance of organization culture (OC) and training on employee performance by using the job satisfaction variable as a mediating variable at PT. Kokoh Semesta. By using a quantitative research design with an explanatory survey method, namely data collection using a questionnaire with a Likert scale model. The sample collection of organic employee respondent data is 125 respondents. Structural Equation Modeling (SEM) PLS Version 4.0.8 is used as a tool to process data. In this study using four variables, seventeen dimensions and thirty-eight indicators. There have seven hypothesis, namely: 1) OC on employee performance. 2) Training on employee performance, 3) Job Satisfaction on employee performance, 4) OC on Job Satisfaction 5) Training on Job Satisfaction, 6) Job Satisfaction mediates the not effect of Training on employee performance, 7) OC the effect of Job Satisfaction on employee performance.